2021
DOI: 10.1111/1471-0307.12767
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating Coalho cheese by origin through near and middle infrared spectroscopy and analytical measures. Discrimination of Coalho cheese origin

Abstract: Discriminating traditional Coalho cheese by origin is important to ensure authenticity. The middle and near infrared spectroscopy and analytical measures associated with different chemometric approaches were used to characterise and discriminate Coalho cheese from different mesoregions of the State of Bahia, Brazil. Principal Component Analysis and Linear Discriminant Analysis were able to show the difference between cheeses. where better discrimination was observed using near infrared spectroscopy, which form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 18 publications
1
13
1
1
Order By: Relevance
“…As higher amounts of inulin are known for decreasing moisture and increasing total solids (Giri, Kanawjia and Singh, 2017), the addition of 1% inulin in coalho cheese is indicated, since low moisture is related to hardness problems in cheese (Fox et al, 2017). On the other hand, in other studies, the moisture content showed higher values between 37.46% and 51.34% for Coalho cheeses (Silva et al, 2021a) even in semihard cheese made with alternative milk species (Silva et al, 2021b) in accordance with characteristics for this type of cheese. Fat differed (P < 0.05) only in the treatment with inulin, presenting the highest content.…”
Section: Physicochemical Characteristics Of Developed Cheesesmentioning
confidence: 53%
“…As higher amounts of inulin are known for decreasing moisture and increasing total solids (Giri, Kanawjia and Singh, 2017), the addition of 1% inulin in coalho cheese is indicated, since low moisture is related to hardness problems in cheese (Fox et al, 2017). On the other hand, in other studies, the moisture content showed higher values between 37.46% and 51.34% for Coalho cheeses (Silva et al, 2021a) even in semihard cheese made with alternative milk species (Silva et al, 2021b) in accordance with characteristics for this type of cheese. Fat differed (P < 0.05) only in the treatment with inulin, presenting the highest content.…”
Section: Physicochemical Characteristics Of Developed Cheesesmentioning
confidence: 53%
“…2020; Silva et al . 2021), and climatic or seasonal fluctuations were carried out, considering variations in the content and profile of fatty acids and volatile compounds in milk and cheese (González‐Martín et al . 2011a).…”
Section: Cheese Authenticitymentioning
confidence: 99%
“…As for the identification of origin, most investigations with the NIR involved differentiation by geographical origin (Silva et al . 2021), mainly of cheeses with protected origin (Cattaneo et al . 2008; Oca et al .…”
Section: Application Of Spectroscopic Techniques For Cheese Authentic...mentioning
confidence: 99%
See 2 more Smart Citations